Range-shifter effects on the stray field in proton therapy measured with the variance–covariance method - Eliasson, Linda; Lillhök, Jan; Bäck, Torbjörn; Billnert-Maróti, Robert; Dasu, Alexandru; Liszka, Malgorzata (Frontiers in Oncology, 2022)
Measurements in the stray radiation field from a proton therapy pencil beam at energies 70~MeV and 146~MeV were performed using microdosimetric tissue-equivalent proportional counters (TEPCs). The detector volumes were filled with a propane-based tissue-equivalent gas at low pressure simulating a mean chord-length of 2~\textmu m in tissue. Investigations were performed with and without a beam range shifter, and with different air gaps between the range shifter and a solid water phantom. The absorbed dose, dose-mean lineal energy and the dose equivalent were determined for different detector positions using the variance-covariance method. The influence from beam energy, detector- and range shifter positions on absorbed dose, LET and dose equivalent were investigated. Monte Carlo simulations of the fluence, detector response, and absorbed dose contribution from different particles were performed with MCNP~6.2. The simulated dose response for protons, neutrons and photons were compared with, and showed good agreement with previously published experimental data. The simulations also showed that the TEPC absorbed dose agrees well with the ambient absorbed dose for neutron energies above 20~MeV The results illustrate that changes in both dose and LET variations in the stray radiation field can be identified from TEPC-measurements using the variance-covariance method. The results are in line with the changes seen in the simulated relative dose contributions from different particles associated with different proton energies and range shifter settings. It is shown that the proton contribution scattered directly from the range shifter dominates in some situations, and although the LET of the radiation is decreased, the ambient dose equivalent is increased up to a factor of three.